Bargaining and the theory of cooperative games John Nash and beyond - Thomson, William 1949-. (Cheltenham, UK Edward Elgar, 2010)
This book explores game theory's development as a tool to understand economic behavior.
Acquired through Health Policy Development Program (HPDP) research grant.
Keywords: Nash, John F. -- Jr. -- 1928-2015.; Negotiation -- Mathematical models; Collective bargaining -- Econometric models; Game theory